Urgensi Rancangan Undang-Undang Masyarakat Adat Ditinjau dari Konflik Warga Adat Toruakat di Suladesi Utara - Suandi Wirdana (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2022)
Conflicts that occur between The Indigenous Peoples of Toruakat and PT. Bulawan Daya Lestari, in Bolaang Mongondow – North Sulawesi, which resulted in 1 (one) indigenous person being killed and 4 (four) other indigenous people injured, can be said to reveal the fact that the Government cannot be present to protect indigenous peoples. Protection, fulfillment, and recognition of indigenous peoples should be related to the substance of human rights in the Constitution of the Republic of Indonesia of 1945. The existence of confirmation in the constitution is not only limited to the recognition of the constitutional rights of indigenous peoples but also must ensure the fulfillment of these constitutional rights.tttttttttt The occurrence of such conflicts can ultimately show an urgency to the Indigenous Peoples Bill. This writing aims to find out and analyze the speed of the Indigenous Peoples Bill reviewed from the conflict of Indigenous Peoples toruakat in North Sulawesi. The method used in this study is a normative juridical method, with secondary data sources as the primary data, then the collected data is analyzed qualitatively... Keywords: Urgency of Draft Law, Indigenous Peoples